Ontological and Ethical Implications of Direct Nuclear Reprogramming - Magill, Gerard (Kennedy Institute of Ethics journal, 2009)
Scientific breakthroughs rarely yield the potential to engage a foundational ethical question. Recent studies on direct reprogramming of human skin cells reported by the Yamanaka lab in Japan and the Thomson lab in Wisconsin suggest that scientists may have crossed both a scientific and an ethical threshold. The fascinating science of direct nuclear reprogramming highlights empirical data that may clarify the ontological status of cellular activity in the early stages of what could become a human fetus and justify ethical options for research in this controversial field. The ontological and ethical implications that accrue here are connected with the biological or natural potentiality of these cells.